2016
DOI: 10.1111/jcpe.12623
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled, multicentre clinical trial of post‐extraction alveolar ridge preservation

Abstract: AimTo compare the effectiveness of two‐ridge preservation treatments.Materials and MethodsForty subjects with extraction sockets exhibiting substantial buccal dehiscences were enrolled and randomized across 10 standardized centres. Treatments were demineralized allograft plus reconstituted and cross‐linked collagen membrane (DFDBA + RECXC) or deproteinized bovine bone mineral with collagen plus native, bilayer collagen membrane (DBBMC + NBCM). Socket dimensions were recorded at baseline and 6 months. Wound clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 18 publications
5
48
1
1
Order By: Relevance
“…Minimal dimensional alteration within 2 mm were shown in both horizontal and vertical aspects, but with large variations. These were in agreement with a recent multicenter clinical study of grafting at buccal‐bone‐deficient extraction sockets18 showing significantly larger dimensional alterations and a much larger standard deviation (2–4 mm) than previous results for intact socket grafting. Previous clinical studies19 of alveolar ridge preservation in intact extraction sockets have found minimal changes in the horizontal and vertical dimensions by grafting xenogenous and allogenous bone substitutes, with small ranges for each value (around 1 mm in most of these studies).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Minimal dimensional alteration within 2 mm were shown in both horizontal and vertical aspects, but with large variations. These were in agreement with a recent multicenter clinical study of grafting at buccal‐bone‐deficient extraction sockets18 showing significantly larger dimensional alterations and a much larger standard deviation (2–4 mm) than previous results for intact socket grafting. Previous clinical studies19 of alveolar ridge preservation in intact extraction sockets have found minimal changes in the horizontal and vertical dimensions by grafting xenogenous and allogenous bone substitutes, with small ranges for each value (around 1 mm in most of these studies).…”
Section: Discussionsupporting
confidence: 92%
“…Based on previous results for the mean and standard deviation of horizontal changes in the ridge dimensions in two experimental groups,18 the effect size was calculated as 0.74. About 40 sites per group were required in the present study, and so 50 sites per group were used on the assumption of a dropout rate of 25%.…”
Section: Methodsmentioning
confidence: 99%
“…There being no significant difference might be attributable to the characteristics of the bone substitute: the collagen component of DBBM‐C seems to contribute the stability of the augmentation. Previously, one study using DBBM‐C only (25%) (Heberer et al, ) demonstrated a similar level of new bone formation as the studies using DBBM‐C + NBCM (26%–30%) (Cardaropoli et al, ; Scheyer et al, ). Comparable soft tissue thickness and minimal fibrous tissue ingrowth into the hard tissue area in both groups also underlines the advantages of DBBM‐C, despite disoriented collagen fibres and some scattered DBBM particles observed in the soft tissue area of test group 2.…”
Section: Discussionmentioning
confidence: 68%
“…The natural repair response of an intact socket after tooth extraction is composed of bone resorption and neoformation (Devlin & Ferguson, 1991). In order to increase the predictability of implant therapy and esthetic outcomes, different techniques using a variety of materials were used to limit alveolar ridge resorption following tooth extraction (Araújo & Lindhe, 2009;Araújo, Silva, Misawa, & Sukekava, 2000;Barone et al, 2008;Jung et al, 2013;Meloni et al, 2015;Nart et al, 2017;Natto et al, 2017;Scheyer et al, 2016). A recent systematic review (Avila-Ortiz, Chambrone, & Vignoletti, 2019) evaluating radiographic outcomes found a significant reduction in the vertical ridge resorption, while the horizontal resorption was inconsistent.…”
Section: Introductionmentioning
confidence: 99%